Analysis of Traditional Market Management in Improving Millennial Consumer Services Through Cleanliness and Security from a Sharia Economic Perspective (Paiton Probolinggo New Market Study) - Musthofa Syukur; Fivia Saddha Inayah (Yayasan Azhar Amanaa Yogyakarta, 2026)
Paiton New Market in Probolinggo Regency is a strategically located traditional market that plays a vital role in meeting community needs. Amidst competition from modern markets and digital platforms, improving services, particularly in terms of cleanliness and security, is key to maintaining market attractiveness. This study aims to examine how traditional market management, particularly in terms of cleanliness and security, can contribute to service improvements and re-attract millennial consumers to shop at Paiton New Market from a sharia economic perspective. The study employed a qualitative case study approach using interviews, observation, and documentation. Data reduction, presentation, and conclusions were analyzed through triangulation of sources and techniques. The results show that Paiton New Market implements strategies to attract consumers by improving its cleanliness and security services. Cleanliness is maintained through scheduled routine cleanings, the placement of trash bins in several locations throughout the market, and collaboration between market management and vendors to maintain a clean environment. Security personnel guard the market area, monitor activities, and maintain order for vendors and visitors. From a sharia economic perspective, these cleanliness and security services reflect the values ​​of trust, responsibility, and shared well-being. With good management in both aspects, Pasar Baru Paiton provides a sense of security and comfort for visitors, attracting consumers, especially millennials, to shop at traditional markets.